Laminar natural convection heat transfer in a shed roof with or without eave for summer season - Öztop, Hakan Fehmi; Varol, Yasin; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2007)
Natural convection heat transfer and fluid flow have been examined numerically in a shed roof with or without eave for summer-day boundary condition. This boundary condition refers to hot isothermal inclined surface and eave, and cold isothermal bottom wall of roof due to air-conditioning of the room. Governing equations of natural convection are written in streamfunction-vorticity form and solved with the finite difference technique for laminar, two-dimensional, and steady-state regime. The successive under relaxation (SUR) method is used to solve linear algebraic equations. The numerical procedure adopted in the present study yields consistent performance over a wide range of parameters as AR = H/L from 0.25 to 1, ratio of eave length E = L/m, where m values are m = 3, 5 and 7, and Rayleigh numbers from 10(3)-10(7). The value of E is considered as 0 (zero) for roof without eave. The obtained results show that eave length and aspect ratio are the most effective parameters on heat transfer for the same Rayleigh numbers. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: numerical heat transfer; natural convection; shed roof; eave